THE EFFECT OF COOPERATIVE LEARNING MODEL STAD TYPE (STUDENT TEAMS ACHIEVEMENT DIVISIONS) AND ABILITY TO MAKE CONCEPT MAP TOWARDS LEARNING OUTCOME OF X CLASS SMK MUHAMMADIYAH CILEGON - Dwi Pujianti (Universitas Sultan Ageng Tirtayasa, 2017)
This study was aimed to determine the effect of cooperative learning model STAD and the ability to make a concept maps on learning outcomes x grade biology students at SMK Muhammadiyah Cilegon. This study population is the class x majoring in nursing with a total sample of 48. The reserch was conducted in November 2015. The research method using Quasi Experiment with a design by level and using ANOVA two way. The results showed there are differences in the biology of learning outcomes significantly between cooperative learning model STAD and conventional learning models. As well there is an interaction between cooperative learning model type STAD with the ability to make a concept map.